"The Paradox of Narcissus and Echo in the Instagram Pond" in Light of the Selfie Culture from Freudian Evolutionary Psychology: Self-Loving and Confident but Lonely. Issue 4 (2nd October 2018) - Jin, Seunga Venus; Ryu, Ehri
Abstract : Drawing from the Freudian evolutionary psychology of narcissism and the literature on social media popularity, this article addresses the central theme revolving around "The Paradox of Digital Narcissists in the Instagram Pond" in light of the selfie/groupie culture. A cross sectional survey was conducted among 398 Instagram users (236 males and 162 females) recruited from Amazon M-Turk. Structural equation modeling analyses using Mplus 7.4 propose an integrative model of narcissism and reveal dynamic relationships among users' narcissism, self-discrepancy, self-confidence, intrasexual competition for mates, need to belong, need for popularity, loneliness, number of selfie/groupie posts on Instagram, and number of Instagram followers/followings.